The Ways Of Learning Phraseologizms With Components Expressing Currency Units In Teaching Process - Azimbayeva Dilafruz Abdijabbarovna (Euro Asian Journal Publishing, 2024)
A phraseological unit may extend across sentence boundaries and even large stretches of text, a web of unique interrelationships of figurative and direct meanings, and associative links. Phraseology was investigated in a great number of researches works. The linguistic nature of phraseological unit has been explored thoroughly nowadays. The main difficulties of this sphere are faced in understanding idiomatic expressions in English. Phraseologizms with components expressing currency units are considered by many researchers as the colorful side of the language. Therefore, learners must see the language through rose-colored glasses to learn every single item that leads to proficiency. In fact, the level of command of idioms serves as an important indicator of target language proficiency. Teaching and learning phraseological units helps to disclose the cognitive processes of the mind in creative thinking. At the same time, it facilities the emergence of the other language skills: speaking, reading and etc. Also, it can lead to significant gains in lexicological and stylistic awareness which involves a conscious perception and understanding of: changes in the base form and meaning of the phraseological unit, associative links and their networks, stylistic cohesive in the text and the creation of a new meaning in context.
Keywords: phraseological unit; figurative; direct; proficiency